The Effects of Trimetazidine and Sildenafil on Bilateral Cavernosal Nerve Injury Induced Oxidative Damage and Cavernosal Fibrosis in Rats - Atilgan, Dogan (Hindawi Publishing Corporation, 2014)
Aim. The aim of this study was to compare the effects of sildenafil and trimetazidine on bilateral cavernosal nerve injury-induced oxidative damage and fibrotic changes in cavernosal tissue in rat model. Material and Methods. A total of 32 male Sprague-Dawley rats were randomly divided into 4 groups; each group consist 8 rats (control, BCI, BCI + TMZ, and BCI + sildenafil groups). Tissue superoxide dismutase (SOD), malondialdehyde (MDA), and protein carbonyl (PC) levels were determined biochemically and distribution of cavernosal fibrosis density among groups was performed histopathologically. Results. Tissue SOD levels in BCI group were significantly lower than the control group (P < 0.05). Tissue MDA and PC levels in BCI group were significantly higher than the control group (P < 0.05). TMZ and sildenafil administration significantly increased tissue SOD levels (P < 0.05) and reduced tissue MDA and PC levels (P < 0.05). Histologically, the degree of cavernosal fibrosis and collagen density was higher in BCI group in comparison to control, TMZ-treated, and sildenafil-treated groups. Conclusion. BCI caused oxidative damage and increased cavernosal fibrosis in rat penis. TMZ and sildenafil treatment decreased oxidative damage and reduced the degree of fibrosis in penile tissue due to BCI.